Kelengkapan Administrasi Guru dalam Pembelajaran PKN Siswa Kelas VIII MTs. Al Kautsar Desa Ranggo Kecamatan Pajo Kabupaten Dompu Tahun Pelajaran 2019/2020 - Fitriani (Jurnal LENTERA: Jurnal Studi Pendidikan, 2020)
This study aims to find out 1). What is the completeness of the administration of teachers in learning Civics students of class VIII MTs. Al-Kautsar Ranggo Village 2019-2020 Academic Year, 2). How is the completeness of the administration of the teacher in class VIII student learning MTs. Al-Kautsar Ranggo Village 2019-2020 Academic Year. The research method used is field research, namely research that studies intensively about a person's background, social interaction, individuals, groups, institutions, and society. In this study, data collection was carried out using the method: Observation Method (Observation), Interview Method (Interview), and Documentation Method. Based on the results of the study obtained as follows 1). Teachers in teaching Citizenship Education class VIII MTs. Al-Kautsar Ranggo Village, Pajo Subdistrict, Dompu Regency has prepared teaching (administration) tools so that it is possible to fight in the teaching and learning process, 2). The role of teacher completeness in teaching MTs Citizenship Education. Al-Kautsar, Ranggo Village, Pajo Subdistrict, Dompu Regency really has an important role for teachers and students, so that output is better.